Zmiany w mleczarskiej bazie surowcowej po przystąpieniu Polski do Unii Europejskiej - Iwan, Bolesław (Changes in Raw Milk Basis after the Accession of Poland to the European Union, 2005)
The raw material basis is the main part of all diary sector. After many years there has been a significant change in the raw milk production. There were many positive changes in the raw milk production in the period before the accession of Poland to the EU.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 342-347